2010
DOI: 10.1128/jvi.00595-10
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Affinity of Tospovirus RNA Silencing Suppressor Proteins, NSs, for Various RNA Duplex Molecules

Abstract: The tospovirus NSs protein was previously shown to suppress the antiviral RNA silencing mechanism in plants. Here the biochemical analysis of NSs proteins from different tospoviruses, using purified NSs or NSs containing cell extracts, is described. The results showed that all tospoviral NSs proteins analyzed exhibited affinity to small double-stranded RNA molecules, i.e., small interfering RNAs (siRNAs) and micro-RNA (miRNA)/miRNA* duplexes. Interestingly, the NSs proteins from tomato spotted wilt virus (TSWV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(141 citation statements)
references
References 59 publications
6
130
1
4
Order By: Relevance
“…Other RSSs, as potyviral HCPro and tombusviral P19, show strong sizepreference for small RNAs of 21 nt, and act by preventing small RNA loading in the RNA-induced silencing complex (RISC) (Silhavy et al 2002;Lakatos et al 2004;Hemmes et al 2007). Moreover, it has been suggested that some RSSs, as the protein B2 of the nodavirus Flock house virus and the NSs proteins of some tospoviruses could use both strategies to achieve a more efficient suppression (Chao et al 2005;Schnettler et al 2010). By in vitro EMSA analyses we showed that CVYV P1b interacts specifically with dsRNA molecules (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Other RSSs, as potyviral HCPro and tombusviral P19, show strong sizepreference for small RNAs of 21 nt, and act by preventing small RNA loading in the RNA-induced silencing complex (RISC) (Silhavy et al 2002;Lakatos et al 2004;Hemmes et al 2007). Moreover, it has been suggested that some RSSs, as the protein B2 of the nodavirus Flock house virus and the NSs proteins of some tospoviruses could use both strategies to achieve a more efficient suppression (Chao et al 2005;Schnettler et al 2010). By in vitro EMSA analyses we showed that CVYV P1b interacts specifically with dsRNA molecules (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…2C) or mammalian cells (Fig. 2D), in contrast to the positive controls, TSWV-NSs and RHBV-NS3, which are potent RSSs used in plant and mammalian cells, respectively (57,58). In both assays, the expression of WNV NS1, NS3, and NS5 was confirmed by Western blot analysis (data not shown).…”
Section: Wnv Nonstructural Proteins Do Not Suppress Rnai In Mammalianmentioning
confidence: 81%
“…The binding reaction was performed as previously described (24,58). A total of 0.5 nM radiolabeled RNA was incubated for 20 min at room temperature with ϳ2 g of total protein from the cell extract.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations